2011
DOI: 10.1177/000313481107700627
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Ultrasound Can Decrease the Re-excision Lumpectomy Rate in Patients with Palpable Breast Cancers

Abstract: Positive margins occur in 15 to 69 per cent of patients undergoing lumpectomy. The current study was performed to evaluate intraoperative ultrasound in patients undergoing lumpectomy for palpable breast cancer. A retrospective chart review was performed of patients with palpable cancer who underwent lumpectomy with intraoperative ultrasound from 2004 to 2009. Each patient was matched with two patients who underwent lumpectomy alone over the same time period. Matching criteria included tumor size, clinical stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
1
26
0
2
Order By: Relevance
“…12,[20][21][22] Although the use of US-guided localization has not always been associated with better results, 20 most studies have demonstrated its superiority to palpation-guided tumorectomy regarding surgical margins and re-excision rates. 19,21,22 In agreement with this finding, we found that US-guided tumor excision was associated with a reduced rate of second operations. The excision volume was not significantly larger than the median excision volume in the palpation-guided group and was comparable with that of other reports.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…12,[20][21][22] Although the use of US-guided localization has not always been associated with better results, 20 most studies have demonstrated its superiority to palpation-guided tumorectomy regarding surgical margins and re-excision rates. 19,21,22 In agreement with this finding, we found that US-guided tumor excision was associated with a reduced rate of second operations. The excision volume was not significantly larger than the median excision volume in the palpation-guided group and was comparable with that of other reports.…”
Section: Discussionsupporting
confidence: 88%
“…18 Several groups have since tested the feasibility and security of the method for the localization of nonpalpable breast cancers and compared it with the standard radio-guided and wireguided localization techniques. 12,[19][20][21][22][23][24][25] These studies demonstrated the superiority of US-guided localization with regard to obtaining clear surgical margins. Furthermore, intraoperative US could facilitate wire-guided lumpectomy, leading to lower rates of positive margins (26).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Other studies that have used ultrasound to mark tumor boundaries on the skin have also shown ▶ Table 4 Overview of the tumor-free margin distance and residual tumor burden in patients for whom reoperation was recommended. a reduction in R1 status [19,21]. We favor immediate intraoperative visualization.…”
Section: Discussionmentioning
confidence: 98%